Meanings and affectivity in the ‘Creole Seeds Guardians Movement in Anchieta/SC (Emancipação, 2026)
The article aims to understand the meanings of seed conservation in relation to the affective bonds that farmers maintain with the continuation of the “Guardians of Creole Seeds” movement in Anchieta, Santa Catarina, Brazil. Creole seeds are currently at risk of disappearing. The guardians ofthese seeds strive to preserve them while also seeking autonomy in rural life. Understanding the affective dimensions embedded in resistance  movements against agribusiness enables a deeper exploration of possible responses to the challenges faced by rural communities in Brazil. We adopt dialectical historical materialism as our methodological framework and employ the  Information Construction technique as our  methodological approach. In-depth interviewswere conducted, from which three core themes emerged: a sense of care; an ethical-ecological relationship; and opposition to the dominant  system and its consequences. We conclude that the affects and meanings associated with sustainable actions are fundamental to labor  practices and their environmental impact. For the Guardians, key aspects include care, value beyond profit, and a foundation rooted in tradition and social relations.
Keywords: Affectivity. Social Psychology. Ethical. Social movements.